The impact of pulmonary rehabilitation on sleep quality in patients with chronic obstructive pulmonary disease: A systematic review and meta-analysis - Shuiyan Dai; Chun Shing Kwok (PLoS ONE, 2025)
Background Pulmonary rehabilitation (PR) is a significant component of chronic obstructive pulmonary disease (COPD) management, but whether it has any impact on patient sleep quality is unknown. Methods We conducted a systematic review of the literature to evaluate the impact of PR on sleep quality in patients with COPD. Searches of the MEDLINE, EMBASE and Cochrane Library databases were performed, and data were extracted from relevant studies. Meta-analysis with the random effects model was performed to determine if PR is associated with any difference in the Pittsburgh Sleep Quality Index (PSQI). Results A total of 16 studies were included in this review with 1,478 patients, of which 1,169 took part in PR. The PR programmes were variable, some being 8-week programmes while others were 12-week, and some lasted for 6 months. The pooled results of 372 patients suggest that PR is associated with a significant improvement in the PSQI (mean difference 2.33 95% CI 0.46 to 4.20, I2 = 93%, 6 studies). Removal of one study, significantly reduced the statistical heterogeneity and the effect size (mean difference 0.91 95% CI 0.35–1.48, I2 = 0%, 5 studies). For other outcomes such as sleep onset latency, wake after sleep onset, total sleep time, sleep efficiency, and number of awakenings, there were no consistencies to suggest any benefit associated with PR. Conclusions PR appears to be associated with improvements in sleep quality in patients with COPD. More studies are needed to determine what the ideal PR programme is that best improves sleep quality and whether certain patients benefit more compared to others.